124k views
1 vote
Rearrange this for z


4z {}^(3) = \frac{(x {}^{ (1)/(2) }y {}^( - 3)z) {}^(2) }{ y - s }

User Ziomara
by
6.4k points

2 Answers

3 votes

Answer:

z = x/[4y⁶(y - 8)]

Explanation:

Distribute the powers

4z³ = (x × y^-6 × z²)/(y - 8

Divide both sides by 4z²

z = (x × y^-6)/4(y - 8)

z = x/[4y⁶(y - 8)]

User Stephan Stamm
by
5.9k points
4 votes


4z^3=((x^(1/2)y^(-3)z)^2)/(y-s)=((x^(1/2)y^(-3))^2z^2)/(y-s)\\4(z^3)/(z^2)(=4z)=((x^(1/2)y^(-3))^2)/(y-s)\\z = ((x^(1/2)y^(-3))^2)/(4(y-s))

User Ebram Khalil
by
5.8k points